Functional Status of Patients After Transcatheter Aortic Valve Replacement Surgery in the Acute Care Setting. Issue 1 (January 2020) - Fick, Ann; Tymkew, Heidi; Cousins, Emily; Bess, Lauren; Halpin, Laura; Pasch, Allyson; King, Shawn; Rosentreter, Caitlin; Arroyo, Cassandra; Oluwole-Sangoseni, Olaide
Abstract : Purpose: Transcatheter aortic valve replacement is a minimally invasive treatment option for patients with aortic stenosis. This study aimed to describe the functional status and determine relationships between patient characteristics, such as age and functional outcomes, following a transcatheter aortic valve replacement procedure in the acute care setting. Methods: Retrospective chart review of 100 patients. Patients were divided into 4 groups: ⩽69, 70 to 79, 80 to 89, and 90-plus years of age. General demographics, Functional Status Score for the Intensive Care Unit, and ambulation distance were collected. Results: Mean age was 79.7 (SD = 8.3) years with 56% female. The first day after surgery, 78% were able to participate in out-of-bed activities. Significant improvement in ambulation distance and Functional Status Score for the Intensive Care Unit scores from evaluation to discharge ( P < .001) were noted in patients receiving 2 or more visits. No significant differences were found between age groups and outcome variables except that patients in the 90-plus age group were more likely to use an assistive device prior to surgery ( P = .004). Conclusions: Patients' status post–transcatheter aortic valve replacement demonstrated improvement in their functional mobility during a short length of stay and were typically discharged home. Age did not appear to significantly impact the patients' ability to participate in early mobility or influence their discharge location.